2022
DOI: 10.3390/foods11091330
|View full text |Cite
|
Sign up to set email alerts
|

Study on the Flavor Compounds of Fo Tiao Qiang under Different Thawing Methods Based on GC–IMS and Electronic Tongue Technology

Abstract: “Fo Tiao Qiang” is a famous dish with Chinese characteristics. It is delicious, rich in materials, and high in nutritional value. Through physical and chemical analysis, electronic tongue, gas chromatography–ion mobility spectroscopy, and other technologies, the present study explored the quality characteristics and flavor differences of Fo Tiao Qiang by using different thawing methods (natural thawing, ultrasonic thawing, microwave thawing, and water bath thawing). The results show that the protein content wa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 25 publications
1
5
0
Order By: Relevance
“…The colors indicate the signal strength of the compounds, with the white color as the lower concentration and the red color as the higher concentration; the intensity increases as the color deepens. After the data was normalized, each point on the right side of the reactive ion peak marked a volatile flavor substance or its dimer [ 25 , 26 ].…”
Section: Resultsmentioning
confidence: 99%
“…The colors indicate the signal strength of the compounds, with the white color as the lower concentration and the red color as the higher concentration; the intensity increases as the color deepens. After the data was normalized, each point on the right side of the reactive ion peak marked a volatile flavor substance or its dimer [ 25 , 26 ].…”
Section: Resultsmentioning
confidence: 99%
“…The sea buckthorn fermented juice was identified for flavor compounds by GC–IMS, as described by Lin et al [ 45 ] with slight modifications.…”
Section: Methodsmentioning
confidence: 99%
“…This conclusion was supported by Samantaray et al (2021), who found that the MP solubility of catla, rohu, and mrigal samples increased by 2.06%, 1.96%, and 2.13%, respectively, relative to that of the fresh control group after the first freezethaw cycle. Furthermore, several thawing effects, such as UT-induced cavitation, can interrupt hydrophobic interactions in the intermolecular cross-linking responsible for MP aggregation, greatly increasing the solubility of MPs (Lin et al, 2022). This was confirmed by Wang et al (2020a), who found that the particle size distribution of MPs after UT was similar to that of the control sample (p < .05) because the turbulence and microflow generated by the ultrasound could destroy the non-covalent bonds between MP molecules, thus reducing MP aggregation (Zhang et al, 2021b).…”
Section: Decline In Solubility or Extractability Of Mpsmentioning
confidence: 99%
“…(2021), who found that the MP solubility of catla, rohu, and mrigal samples increased by 2.06%, 1.96%, and 2.13%, respectively, relative to that of the fresh control group after the first freeze–thaw cycle. Furthermore, several thawing effects, such as UT‐induced cavitation, can interrupt hydrophobic interactions in the intermolecular cross‐linking responsible for MP aggregation, greatly increasing the solubility of MPs (Lin et al., 2022). This was confirmed by Wang et al.…”
Section: Thawing‐induced Mp Denaturationmentioning
confidence: 99%
See 1 more Smart Citation